The soluble cytoplasmic tail of CD45 (ct‐CD45) in human plasma contributes to keep T cells in a quiescent state. Issue 1 (31st October 2016) - Puck, Alexander; Hopf, Stefan; Modak, Madhura; Majdic, Otto; Cejka, Petra; Blüml, Stephan; Schmetterer, Klaus; Arnold‐Schrauf, Catharina; Gerwien, Jens G.; Frederiksen, Klaus S.; Thell, Elisabeth; Leitner, Judith; et al.
Abstract : The cytoplasmic tail of CD45 (ct‐CD45) is a soluble factor in steady‐state adult human plasma. ct‐CD45 levels may be altered during development and disease. It appears to be an extrinsic contributor to the maintenance of T‐cell quiescence by enforcing a transcriptional program including potential quiescence regulators KLF2 and SLFN12. Abstract : The cytoplasmic tail of CD45 (ct‐CD45) is proteolytically cleaved and released upon activation of human phagocytes. It acts on T cells as an inhibitory, cytokine‐like factor in vitro. Here, we show that ct‐CD45 is abundant in human peripheral blood plasma from healthy adults compared with plasma derived from umbilical cord blood and plasma from patients with rheumatoid arthritis or systemic lupus erythematosus. Plasma depleted of ct‐CD45 enhanced T‐cell proliferation, while addition of exogenous ct‐CD45 protein inhibited proliferation and reduced cytokine production of human T lymphocytes in response to TCR signaling. Inhibition of T‐cell proliferation by ct‐CD45 was overcome by costimulation via CD28. T‐cell activation in the presence of ct‐CD45 was associated with an upregulation of the quiescence factors Schlafen family member 12 ( SLFN12 ) and Krueppel‐like factor 2 ( KLF2 ) as well as of the cyclin‐dependent kinase (CDK) inhibitor p27kip1 . In contrast, positive regulators of the cell cycle such as cyclin D2 and D3 as well as CDK2 and CDK4 were found to be downregulated in response to ct‐CD45. In summary, we demonstrate that ct‐CD45 is present in human plasma and sets the threshold of T‐cell activation.